KONTRIBUSI PANJANG TUNGKAI DAN KECEPATAN LARI TERHADAP MENGGIRING PADA PERMAINAN SEPAK BOLA - Situmorang, Franciskus Efendi; Atiq, Ahmad; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Sport is one activity to live a healthy and fit life. In exercising, it is not only healthy that is obtained, but with sports activites a person a person will be able to- do get awards for the achievements in sport that have been achieved. The purpose of this study is to determine the relationship of leg muscles strength to-do dribbling result in soccer games at SMA Country 1 Sungai Tebelian extracurriculars. The method used in this research is quantitative descriptive method, the method used in this study is a survey method with correlation techniques. The data collection technique uses test and measurements. First do a leg muscle strength test and a running speed test and a ball dribbling test in a soccer game. Data analysis techniques start with problem formulation, preparation of measurement tools ( data collection instruments ), then data collection activities. The research results explain the results of research conducted and processed using SPSS data. The research result were processed through a series of tests which became a data collection tool. As for the results of this study, out of 30 research samples, it was found that 5 students got very good scores (16%), 9 students got good criteria (25%), 7 students got criteria (6%), and 7 students get the criteria less than once (23%),. The conclusion from the researcher that there is a correlation shows that the correlation coefficient between leg length and a soccer dribble results is 0.684. The correlation coefficient test is carried out by consulting the price of r count with r table for a : 5% with N: 30 is 0.468